Granulosa cell-derived extracellular vesicles mitigate the detrimental impact of thermal stress on bovine oocytes and embryos - Menjivar, Nico G.; Gad, Ahmed; Gebremedhn, Samuel; Ghosh, Soham; Tesfaye, Dawit (Frontiers in Cell and Developmental Biology, 2023)
Climate change-induced global warming results in rises in body temperatures above normal physiological levels (hyperthermia) with negative impacts on reproductive function in dairy and beef animals. Extracellular vesicles (EVs), commonly described as nano-sized, lipid-enclosed complexes, harnessed with a plethora of bioactive cargoes (RNAs, proteins, and lipids), are crucial to regulating processes like folliculogenesis and the initiation of different signaling pathways. The beneficial role of follicular fluid-derived EVs in inducing thermotolerance to oocytes during in vitro maturation (IVM) has been evidenced. Here we aimed to determine the capacity of in vitro cultured granulosa cell-derived EVs (GC-EVs) to modulate bovine oocytes’ thermotolerance to heat stress (HS) during IVM. Moreover, this study tested the hypothesis that EVs released from thermally stressed GCs (S-EVs) shuttle protective messages to provide protection against subsequent HS in bovine oocytes. For this, sub-populations of GC-EVs were generated from GCs subjected to 38.5°C (N-EVs) or 42°C (S-EVs) and supplemented to cumulus-oocyte complexes (COCs) matured in vitro at the normal physiological body temperature of the cow (38.5°C) or HS (41°C) conditions. Results indicate that S-EVs improve the survival of oocytes by reducing ROS accumulation, improving mitochondrial function, and suppressing the expression of stress-associated genes thereby reducing the severity of HS on oocytes. Moreover, our findings indicate a carryover impact from the addition of GC-EVs during oocyte maturation in the development to the blastocyst stage with enhanced viability.